2020
DOI: 10.1021/acs.bioconjchem.0c00551
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pretargeting Based on Cysteine-Selective Antibody Modification with IEDDA Bioorthogonal Handles for Click Chemistry

Abstract: Pretargeted imaging has emerged as an effective multistep strategy aiming to improve imaging contrast and reduce patient radiation exposure through decoupling of the radioactivity from the targeting vector. The inverse electron-demand Diels− Alder (IEDDA) reaction between a trans-cyclooctene (TCO)conjugated antibody and a labeled tetrazine holds great promise for pretargeted imaging applications due to its bioorthogonality, rapid kinetics under mild conditions, and formation of stable products. Herein, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…MALDI-TOF mass spectrometry and denaturing SDS-PAGE analyses showed that approximately 2.4 TCO groups were attached on the heavy chain of the antibody, while immunoreactivity of the conjugate was almost not influenced by the modifications (94%). Another site-specific labeling method based on reaction between cysteine and carbonylacrylic group was recently reported [81]. 5-OH-TCO was functionalized with a carbonylacrylic group (20) and conjugated to THIOMAB LC-V205C, a modified anti-HER2 antibody with cysteines in the light chain.…”
Section: Radiolabeling Of Monoclonal Antibodies (Mabs) With Short-lived Radionuclides and Pretargetingmentioning
confidence: 99%
“…MALDI-TOF mass spectrometry and denaturing SDS-PAGE analyses showed that approximately 2.4 TCO groups were attached on the heavy chain of the antibody, while immunoreactivity of the conjugate was almost not influenced by the modifications (94%). Another site-specific labeling method based on reaction between cysteine and carbonylacrylic group was recently reported [81]. 5-OH-TCO was functionalized with a carbonylacrylic group (20) and conjugated to THIOMAB LC-V205C, a modified anti-HER2 antibody with cysteines in the light chain.…”
Section: Radiolabeling Of Monoclonal Antibodies (Mabs) With Short-lived Radionuclides and Pretargetingmentioning
confidence: 99%
“…This choice was motivated by the higher in vivo stability and by the easy separation of the radiolabelled [ 111 In]In-DOTA-Tz derivative from the unreacted chelator. Given a future in vivo application of such clickable chelator, this advantage might allow to achieve radiocomplexes with higher specific activity reducing the competition risk for the in vivo click reaction with the TCO counterpart (31).…”
Section: Clickable [ 111 In]in-radiocomplexesmentioning
confidence: 99%
“…Targeting the abundant, surface-exposed and charged Lys residues generally results in the formation of highly heterogeneous mixtures and may significantly impact biological binding. Promising approaches have recently been described to overcome the initial limitations of Lys 10,11 and Cys 12,13 modifications, and much effort is now dedicated to selectively target less exploited amino acids such as methionine, 14 tryptophan, 15,16 histidine 17,18 or tyrosine (Y). 19,20 Y usually occurs at low frequency in proteins (<5%) and is partially buried in the surface, offering unique opportunities for controlled labelling of the most reactive residues.…”
Section: Introductionmentioning
confidence: 99%